A randomized, double-blind, placebo-controlled trial for Yi-Qi Hua-Yu tong-sui granule in the treatment of mild or moderate cervical spondylotic myelopathy. Issue 33 (14th August 2020) - Xu, Chongqing; Zhou, Xiaoning; Tong, Zhengyi; Ma, Junming; Ye, Jie; Xu, Jinhai; Mo, Wen
Abstract: Background: Neck pain, sensory disturbance and motor dysfunction in most patients suffered cervical spondylotic myelopathy (CSM). However, some conservative treatments are limited by their modest effectiveness. In the other hand, surgical treatment is necessary when symptoms are refractory to conservative treatments and neurological function of the patients has deteriorated. Many patients use complementary and alternative medicine, including traditional Chinese medicine, to address their symptoms. The purpose of the present study is to examine effectiveness and safety of Yiqi-Huayu-Tongsui (YQHYTS) granule, a compound traditional Chinese herbal medicine, on symptoms in patients with mild or moderate CSM. Methods/Design: A randomized, double blinded, placebo-controlled clinical trial to evaluate the efficacy and safety of YQHYTS granule is proposed. 72 patients in Longhua Hospital with the diagnosis of mild or moderate CSM will be randomly allocated into 2 groups, and treated with YQHYTS granule or placebo. The prescription of the trial drugs (YQHYTS granule/placebo) is 20 grams twice a day for 3 months. The primary outcome measurements include visual analog scale, Japanese Orthopedic Association, and Neck Disability Index score. The secondary outcome measurements are electromyogram and Pfirrmann classification. Discussion: YQHYTS granule has been established and applied in Longhua Hospital for many years. As it has a potential benefit in treating mild or moderate CSM, we designed a double-blind, prospective, randomized controlled trial and would like to publish the results and conclusions later. If YQHYTS granule can alleviate neck pain, sensory disturbance, and even motor dysfunction without adverse effects, it may be a unique strategy for the treatment of mild or moderate CSM. Trial registration: Chinese Clinical Trial Registry ID: ChiCTR1900028192. Registered 15 December 2019, Available at: http://www.chictr.org.cn/edit.aspx?pid=46913&htm=4